Influence of the metabolic state during lactation on milk production in modern sows. (25th December 2020) - Costermans, N. G. J.; Soede, N. M.; Middelkoop, A.; Laurenssen, B. F. A.; Koopmanschap, R. E.; Zak, L. J.; Knol, E. F.; Keijer, J.; Teerds, K. J.; Kemp, B.
Abstract : Selection for prolificacy in sows has resulted in higher metabolic demands during lactation. In addition, modern sows have an increased genetic merit for leanness. Consequently, sow metabolism during lactation has changed, possibly affecting milk production and litter weight gain. The aim of this study was to investigate the effect of lactational feed intake on milk production and relations between mobilization of body tissues (adipose tissue or skeletal muscle) and milk production in modern sows with a different lactational feed intake. A total of 36 primiparous sows were used, which were either full-fed (6.5 kg/day) or restricted-fed (3.25 kg/day) during the last 2 weeks of a 24-day lactation. Restricted-fed sows had a lower milk fat percentage at weaning and a lower litter weight gain and estimated milk fat and protein production in the last week of lactation. Next, several relations between sow body condition (loss) and milk production variables were identified. Sow BW, loin muscle depth and backfat depth at parturition were positively related to milk fat production in the last week of lactation. In addition, milk fat production was related to the backfat depth loss while milk protein production was related to the loin muscle depth loss during lactation. Backfat depth and loin muscle depth at parturition were positively related to lactational backfat depth loss or muscle depth loss, respectively. Together, results suggest that sows which have more available resources during lactation, either from a higher amount of body tissues at parturition or from an increased feed intake during lactation, direct more energy toward milk production to support a higher litter weight gain. In addition, results show that the type of milk nutrients that sows produce (i.e. milk fat or milk protein) is highly related to the type of body tissues that are mobilized during lactation. Interestingly, relations between sow body condition and milk production were all independent of feed level during lactation. Sow management strategies to increase milk production and litter growth in modern sows may focus on improving sow body condition at the start of lactation or increasing feed intake during lactation.